Africa in the global agricultural economy in 2030 and 2050 - Sulser, Timothy B.; Mason-D’Croz, Daniel; Islam, Shahnila; Robinson, Sherman; Wiebe, Keith D.; Rosegrant, Mark W. (International Food Policy Research Institute, 2015)
Africa has managed to maintain a favorable environment for growth and poverty reduction in the face of the series of global economic crises in the past couple decades. Part of this is due to Africa’s level of isolation from the global economy, but it is also testament to the resilience of African economies even if they are not experiencing the extraordinary growth seen in South and East Asia (AfDB, OECD, and UNDP 2015). Per capita gross domestic product (GDP) grew at a solid 2 percent per year in the decade leading up to 2012 across all of Africa, with western Africa leading at more than 4 percent growth (ReSAKSS database 2015). This growth has put the average per capita GDP for all of Africa at the threshold of middle-income classification according to the World Bank’s World Development Indicators. Eastern and central Africa lag behind a bit with many low-income nations, while the northern and southern regions are mostly represented by stronger middle-income economies.